Relationship Between Medial Meniscal Extrusion and Cartilage Loss in Specific Femorotibial Subregions: Data From the Osteoarthritis Initiative. Issue 11 (November 2015) - Bloecker, K.; Wirth, W.; Guermazi, A.; Hunter, D. J.; Resch, H.; Hochreiter, J.; Eckstein, F.
Abstract : Objective: Medial meniscal extrusion is known to be related to structural progression of knee osteoarthritis. However, it is unclear whether medial meniscal extrusion is more strongly associated with cartilage loss in certain medial femorotibial subregions than in others. Methods: Segmentation of the medial tibial and femoral cartilage (baseline; 1‐year followup) and the medial meniscus (baseline) was performed in 60 participants with frequent knee pain (mean ± SD ages 61.3 ± 9.2 years, body mass index 31.3 ± 3.9 kg/m 2 ) and with unilateral medial radiographic joint space narrowing (JSN) grades 1–3, using double‐echo steady‐state magnetic resonance images. Medial meniscal extrusion distance and extrusion area (percentage) between the external meniscal and tibial margin at baseline, and longitudinal medial cartilage loss in 8 anatomic subregions were determined. Results: A significant association (Pearson's correlation coefficient) was seen between medial meniscal extrusion area in JSN knees and cartilage loss over 1 year throughout the entire medial femorotibial compartment. The strongest correlation was with cartilage loss in the external medial tibia (r =−0.34, P < 0.01 in JSN; r =−0.30, P = 0.02 in knees without JSN). Conclusion: Medial meniscal extrusion was associated with subsequent medial cartilage loss. The external medial tibial cartilage may be particularly vulnerable to thinning once the meniscus extrudes and its surface is exposed to direct, nonphysiological, cartilage‐to‐cartilage contact.